Factors affecting the University Students’ Mental Health during the 2020 COVID-19 outbreak - Mary Antoniete Tavera Jacinto; Adeline M De Guzman (Journal of Educational, Health and Community Psychology, 2023)
Fear and worry, especially in rural Philippines, harmed youths' mental health during the COVID-19 pandemic. There were 722 Isabela State University students surveyed for mental health. An online descriptive survey described their characteristics, stressors, coping techniques, and epidemic-related mental health hurdles. Depression and anxiety were assessed with the Patient Health Questionnaire -9 and Gender Anxiety Disorder-7. Most 19-20-year-old students reported mild depression and anxiety, with females more affected than males. Financial issues prevented mental health care, affecting academic performance. Other stressors were COVID-19 symptoms, lack of counseling, and social isolation. Exercise, diet, and creativity were also coping techniques. These facts demonstrate that COVID-19's isolation and economic, educational, and mental effects are interrelated. Increased counseling services, telehealth training, seminars, interventions, academic assistance, and mental health technology can help bridge the gap between students, parents, and institutions. Future studies will provide specific therapies for the most affected groups.